The effects of preoperative education, marking and adequate positioning of stoma on self-esteem and the quality of life of patients with intestinal ostomy and their families - Konjevoda, Vesna (Array, 2020)
Aim. The purpose of this systematic review is to examine all available research studies on quality of life of ostomy patients and their families, which is contingent upon the effects of adequate preoperational education, the best and most acceptable ostomy site marking on the patients’ abdomen, and subsequently, the effect on the ostomy patients’ self-esteem. Methods. A literature search was carried out using scientific electronic databases - Science Direct, PubMed and Medline. Analysed period was from 2010 to 2016 in order to get insight into the most recent findings. Search terms included preoperative education, stoma marking, quality of life, self-esteem, influence on family life. Overview of articles was made in three stages. Results. We found 1440 scientific articles. In the first stage, we eliminated 1271 articles because they were unsuitable. In the second stage, we analysed 34 articles and made a conclusion based on 13 full text available articles. Conclusion. The patient is content while being treated in the hospital; however, only after the patient has been released do the hardships occur, which are often the main cause of discontent, isolation, anxiety, and fear – thus resulting in diminished quality of life. Preoperational education and marking the most acceptable place for ostomy procedure significantly affect the self-esteem and the quality of life of ostomy patients and their families. Ostomy patients need to be followed up, and the home care system, as well as the support systems of public health care for patients with a gastrointestinal ostomy, need to be strengthened.